Assessment of genetic variation(s) in BBS10, BBS6, and BBS12 in a family from Sindh, Pakistan diagnosed with Bardet-Biedl Syndrome - Fatima, Sehrish; Amjad, Maryam; Zehra, Faiza; Sher, Khalid; Kumar, Suneel; Saleem, Saima; Zehra, Sitwat (Journal of the Pakistan Medical Association, 2025)
Objective: To analyse the symptoms of Bardet-Biedl Syndrome, and to check the association of BBS10 (Bardet-Biedl syndrome 10 gene), BBS6 (Bardet-Biedl syndrome 6 gene) and BBS12 (Bardet-Biedl syndrome 12 gene) with the pathogenesis of Bardet-Biedl Syndrome. Method: The case-control study was conducted in Karachi in 2019-20, and comprised Bardet-Biedl Syndrome patients and healthy controls from the same family. Blood was drawn from all the subjects for deoxyribonucleic acid extraction. Genotyping was performed by conventional and tetra primer amplification refractory mutation system polymerase chain reaction (T-ARMS-PCR) to identify the possible genetic variations. To validate the results, samples were randomly selected and sent for sequencing. Data was analysed using SPSS 20, while sequencing data was analysed using the Molecular Evolutionary Genetics Analysis X software. Results: Of the 20 subjects with mean age 15.8+/-5.09 years (range: 9-25 years), 8(40%) were cases and 12(60%) were controls. The male-to-female ratio was 1:1. Pedigree analysis revealed that the pattern of inheritance was autosomal recessive. All the 8(100%) cases were obese compared to the controls. Truncal obesity, polydactyly, learning impairment and dysmorphic features, renal pain, olfactory dysfunction, respiratory tract infection and dysphasia were observed in all the 8(100%) cases. The globally reported genetic variants of BBS10 (rs1057516628 and rs1489342987) and BBS12 (rs121918327 and rs587777802) did not indicate any association with the clinical phenotype in the family concerned. The genetic variations of BBS6 (rs1547, rs1545 and rs1351192494), BBS12 (rs309370, rs2292493) and a BBS10 variant (rs35676114) had significant association with the disease. Conclusion: The genetic variations showed confounding effects of BBS10, BBS6 and BBS12 genes which might indicate the epistatic effects of other variants present on different loci. Key Words: Bardet-Biedl syndrome, BBS10, BBS6, BBS12, Genetic variations, Polymorphism.